PENGARUH KESELAMATAN DAN KESEHATAN KERJA (K3) TERHADAP PRODUKTIVITAS KARYAWAN PADA PT. BAROKAH PERKASA GROUP - Ekrin Yohanes Suharyono, Murdiono 1, Eddy Soegiarto 2 (EKONOMIA, 2020)
The research aims to know the influence of: 1). Occupational Safety to the employee productivity on PT. Barokah Perkasa Group. 2). Occupational Health to the employee productivity on PT. Barokah Perkasa Group. 3). Occupational Safety and Health simultaneously to the employee productivity on PT. Barokah Perkasa Group.Population that used in this research are all employee production and repair department of PT. Barokah Perkasa Group, wich are 125 employees. Sample research are 56 respondens by Slovin formula and sampling techniquethat used is random sampling. The analysis tools that used multiple linier regression analysis, hypothesis test, and classic assumption test.The results of the study concluded that: 1). Partially based on the significance of work safety variables a positive and significant effect on employee productivity. 2). Based on the partial significance test, occupational health variables have positive and significant effects on employee productivity. 3). Based on the simultaneous significance test, it is produced that occupational safety and health variables simultaneously have positive and significant effects on employee productivity.